Clinical Case of Complicated Thrombophilia in a Patient with Ulcerative Colitis - S. A. Boldueva; I. V. Yarmosh; A. N. Dolinova; Z. G. Kaloeva; M. Yu. Serkova; V. M. Avramova (Рациональная фармакотерапия в кардиологии, 2020)
This article presents the clinical observation of hereditary thrombophilia, complicated by the formation of a thrombus in the cavity of the right ventricle, in a 40-year-old patient with first diagnosed ulcerative colitis. Despite the standard drug therapy, the patient had a persistent fever. Transthoracic echocardiogram revealed a formation in the right ventricle. A differential diagnosis was made between the vegetation and thrombus. Due to the high risk of infective endocarditis, the antibacterial therapy was started. The addition of deep vein and common iliac vein thrombosis required the exclusion of thrombophilia. Molecular genetic testing allowed to diagnose hereditary thrombophilia: heterozygous carriage of mutations in the genes of factor V Leiden, fibrinogen, platelet receptor for collagen, plasminogen activator inhibitor I. The diagnosis of thrombophilia and ineffectiveness of antibacterial therapy led to the conclusion that there was a thrombus in the right ventricle. The treatment of ulcerative colitis was continued. At the same time, anticoagulant therapy was started, and antibiotics were canceled. As a result, clinical remission of ulcerative colitis, regression of venous thrombosis and complete dissolution of the thrombus in the cavity of the right ventricle were achieved. Ulcerative colitis may be complicated by venous trombosis and hereditary thrombophilia increases this risk.